THE DRUG USE MOTIVATION AMONG MALAYSIAN ATHLETES - vincent Parnabas; Yahaya Mahamood; Julinamary Parnabas; Muhamad Nizam Nazaruddin; Nagoor Meera Abdullah; Mohd Soffian Omar-Fauzee (HUMANITAS: Indonesian Psychological Journal, 2013)
AbstractThe aim of this research was to identify the usage of drugs on athletes by focusing on gender and different categories level of athletes. The sample, which was chosen randomly consisted of 115 athletes, consisting of national athletes (N=35), state athletes (N=35), district athletes (N=19), and university athletes (N=26). Based on gender, the present research consists of 70 male and 45 female athletes. Drug Usage Questionnaire, were used to collect the data. The result showed that the main motive usage of drugsis to win. This research also showed that male athletes use more drugs than females. National or athletes who represent the country are highest in using drugs. Sport psychologists should play an important role by providing therapies to drug addicts’ athletes to curb the usage of drugs. Malaysian government also should prevent athletes who taken drugs from taking part in sport competition.Key Words: coping strategy , district, drugs, representing national, state.